Binder and polymer assisted powder processing - German, Randall M., 1946-; Bose, Animesh (ASM International, 2020)
Binder and Polymer Assisted Powder Processing is an engineering guide to powder-binder-based manufacturing methods. It covers the basic principles, current and emerging practices, implementation, and cost.